Effect of ritonavir on the pharmacokinetics of ethinyl oestradiol in healthy female volunteers - Ouellet, Daniele (Blackwell Science Inc, 1998)
AIMS: To assess the effects of the protease inhibitor ritonavir on the pharmacokinetics of ethinyl oestradiol in healthy female volunteers. METHODS: This was an open-label, single centre study in 23 subjects who received two single doses of oral contraceptive containing 50 μg ethinyl oestradiol on Day 1 (alone) and on Day 29 during concomitant ritonavir. Each subject received 16 days of every 12 h doses of ritonavir from Day 15 through Day 30. Blood samples were collected for serum ethinyl oestradiol concentrations for 48 h after each dose and for plasma ritonavir on Day 29 at 0 and 4 h postdose. RESULTS: Statistically significant decreases in ethinyl oestradiol mean C(max) (−32%) and mean AUC (−41%), and a statistically significant increase in the mean terminal elimination rate constant (+31%) were observed during concomitant ritonavir. The harmonic mean terminal half-life decreased from 17 h to 13 h during concomitant ritonavir. No statistically significant change was noted in t(max). The ratios of means (95% confidence intervals) for C(max) and AUC were 0.682 (0.612–0.758) and 0.595 (0.506–0.694), respectively. The changes in ethinyl oestradiol pharmacokinetics were consistent with an increase in clearance from enzymatic induction of glucuronidation and/or cytochrome P450 hydroxylation. Mean steady-state ritonavir concentrations of 6.5 and 13.4 μg ml(−1) were observed at 0 and 4 h postdose, respectively. CONCLUSIONS: Considering the extent of the decrease in ethinyl oestradiol concentrations, the use of alternate contraceptive measures should be considered when ritonavir is being administered.